Synthesis and Chemical Properties of Diacetylenes with Pyridinium and 4,4′-Bipyridinium Groups - Yamaguchi, Isao; Higashi, Hideo; Kimura, Shunsuke; Sato, Moriyuki (Helvetica chimica acta, 2010)
Diacetylenes (DAs) having a dipolar D‐π‐A structure (D=donor: amino group; π=π‐conjugation core; A=acceptor: pyridinium (Py) and bipyridinium (BPy) groups), i.e., 4 (APBPyDA) and 5 (APPyPyDA), or an A‐π‐A structure, i.e., 7 (DBPyDA) and 8 (PyDA(Cl)), were obtained by 1 : 1 and 1 : 2 reactions of 4,4′‐(buta‐1,3‐diyne‐1,4‐diyl)bis[benzenamine] (APDA; 3) with 1‐(2,4‐dinitrophenyl)‐1′‐hexyl‐4,4′‐bipyridinium bromide chloride (1 : 1 : 1) (1), 1‐(2,4‐dinitrophenyl)‐4‐(pyridin‐4‐yl)pyridinium chloride (2), or 1‐(2,4‐dinitrophenyl)pyridinium chloride (6) (Schemes 1 and 2). The anion‐exchange reactions of 8 with NaI and Li(TCNQ) (TCNQ−=2,2′‐(cyclohexa‐2,5‐diene‐1,4‐diylidene)bis[propanedinitrile] radical ion (1−)) yielded the corresponding I− and TCNQ− salts 9 (PyDA(I)) and 10 (PyDA(TCNQ)). Compounds 10 and 4 exhibited a UV/VIS absorption due to a charge transfer between the TCNQ− and the pyridinium groups and a strong solute–solvent interaction of a dipolar solute molecule in the polar environment, respectively. Compounds 8–10 exhibited photoluminescence in solution, whereas 4 and 7 did not because of the presence of the 4,4′‐bipyridinium quenching groups. Differential‐scanning‐calorimetry (DSC) measurements suggested that the DAs obtained in this study can be converted into poly(diacetylenes) by thermal polymerization.